2020
DOI: 10.6018/cpd.346851
|View full text |Cite
|
Sign up to set email alerts
|

Teaching personal and social responsibility after school: A systematic review

Abstract: Background: Teaching Personal and Social Responsibility (TPSR) has been studied and implemented through physical activity in different backgrounds for over three decades. However, there is no systematized review in the literature concerning the after-school context. Aim: Conducting a systematic review of literature on after-school interventions based on the TPSR model. Methods: This study was driven by the following research questions: Which were the conclusions regarding the implementation of TPSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
7
0
4
Order By: Relevance
“…Another systematic review of 22 studies on TPSR-based programs in PE setting concluded that successful implementation of TPSR contribute to a range of positive behavioral, social, emotional, psychological, and educational outcomes ( Pozo et al, 2018 ). Related to the TPSR implementation in after school setting, a recent systematic review in which 27 papers were selected, 13 of them provided significant experiences and had a positive impact on staff and youngsters who engaged in sports activities ( Baptista et al, 2020 ). Finally, systematic review of 35 studies classified according to the methodology used shows that the application of the TPSR has found positive results in all the studies analyzed ( Sánchez-Alcaraz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review of 22 studies on TPSR-based programs in PE setting concluded that successful implementation of TPSR contribute to a range of positive behavioral, social, emotional, psychological, and educational outcomes ( Pozo et al, 2018 ). Related to the TPSR implementation in after school setting, a recent systematic review in which 27 papers were selected, 13 of them provided significant experiences and had a positive impact on staff and youngsters who engaged in sports activities ( Baptista et al, 2020 ). Finally, systematic review of 35 studies classified according to the methodology used shows that the application of the TPSR has found positive results in all the studies analyzed ( Sánchez-Alcaraz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…En particular, la estrategia de enseñanza enfocada al fomento de la transferencia, la cual solo un entrenador mostró aumento significativo en su aplicación, es ejemplo de ello. A pesar de que el Programa de Responsabilidad Personal y Social ha mostrado efectos positivos en los participantes (Baptista et al, 2020;Sánchez-Alcaraz et al, 2020;Shen et al, 2022) aún hay investigaciones que identifican como área de oportunidad la transferencia de habilidades a otros contextos (Barrero et at., 2017).…”
Section: Discussionunclassified
“…Existe un programa propuesto por Hellison (2011) que busca desarrollar a través del deporte y la actividad física habilidades de vida, específicamente propone la enseñanza de la responsabilidad a nivel personal y social, entendida como una obligación moral respecto a uno mismo y los demás. El programa de Responsabilidad Personal y Social por sus siglas en inglés TPSR, ha sido implementado de manera frecuente en las últimas dos décadas alrededor de todo el mundo, encontrando resultados positivos en cuanto su eficacia (Baptista et al, 2020;Sánchez-Alcaraz et al, 2020;Shen et al, 2022). El TPSR fue diseñado inicialmente para implementarse a través del deporte con población en condiciones de riesgo, sin embargo, su estructura metodológica es fácilmente adaptable a diferentes entornos y poblaciones, por lo que es una de las propuestas más referenciadas en el ámbito ya que ha sido utilizado para el desarrollo psicoemocional como la autoeficacia, la cooperación, la empatía, entre otros (Caballero, 2015;Sánchez-Alcaraz et al, 2020;Shen et al, 2022).…”
Section: Introductionunclassified
“…Estos resultados pueden estar vinculados al énfasis puesto en la intervención para fomentar el esfuerzo, la persistencia en las tareas, la autonomía en la participación y el compromiso con objetivos exigentes pero alcanzables. Nuestros hallazgos van en la línea de estudios previos basados en el MRPS, realizados en el ámbito educativo con niños y adolescentes, que han mostrado asociaciones entre la responsabilidad personal y social y la motivación intrínseca (Escartí, Gutiérrez & Pascual 2011;Baptista, et al, 2020;Li, Wright, Rukavina & Pickering, 2008;Merino, et al, 2019;Sánchez, et al, 2020;Pozo, et al, 2018).…”
Section: Discussionunclassified